134 A Quality Improvement Project—Physiotherapy Caseload Management on the Older Person's Unit. (16th March 2021) - Snape, C; Triteos, N; Wood, C A; Robert, G; Jones, J
Abstract: Introduction: Complex health issues, co-morbidities and the number of patients living with frailty are critical concerns associated with the ageing population (Kojima et al, 2019). In this wider context, there is an emphasis on targeting resources efficaciously within the NHS. A consequence of capacity constraints, inpatient physiotherapy teams across the OPU at a large urban teaching hospital, prioritise their patient caseload, but lack evidence-based guidance on dosage and frequency of physiotherapy intervention, to inform the process. The aim of the quality improvement project was to design and deliver a staff education and training package to facilitate implementation of a newly-developed, evidence-based prioritisation resource. Method: Plan-Do-Study-Act cycles and the Com-B model to influence behaviour changes were employed between October 2019 and March 2020. Stakeholders were engaged throughout the design process. Training to all 11 physiotherapists consisted of familiarisation with the resource through content discussion and "mock-use" training sessions to ensure intra/inter-rater-reliabilty. Physiotherapist staff knowledge and confidence of prioritisation was evaluated by questionnaire. Accuracy of use of the prioritisation tool was determined by comparison of staff prioritisation decision with expert opinion. Results: From the 11 questionnaire responses, pre to post intervention physiotherapy knowledge of the prioritisation categories increased (43% to 100%), physiotherapist rated confidence using the prioritisation tool increased (mean score, 6.9 to 8.2/10) and accuracy of prioritisation of patients improved (mean 42.1% to 92.3%). Conclusion: The education and training package developed to support implementation of the prioritisation tool resulted in improved staff knowledge and confidence of patient prioritisation and increased the accuracy of OPU physiotherapy targeting. This project has highlighted the importance of staff training in resource allocation to ensure that decisions regarding which patients receive physiotherapy intervention are efficacious. This has increased relevance in a department with a large number of rotational staff.